(untitled) (Journal of Medicine, 2011)
This hospital based cross sectional descriptive study was performed to find out the prognostic factors of acute pancreatitis from the available clinical, biochemical, haematological and radiological data. A total of 50 cases were studied. Peak incidence was in the fourth decade. Among the known aetiological factors 18% were due to gallstone disease, 10% alcoholism, 4% pancreatobiliary ascariasis, but 60% were idiopathic. In this study 82% patients were had mild and 18% had severe acute pancreatitis. Overall mortality rate was 6%, mortality was significantly higher (33.33%) in severe acute pancreatitis (33.3% vs 0%). A higher mortality was associated with concomitant medical or surgical diseases, leucocytosis. Other factors associated with a higher mortality were high blood glucose, serum creatinine level and a lower serum albumin and calcium level. This study highlights the need of further study with more detailed recording of relevant data from primary care hospital to find out the clinical pattern of complications and prognostic factors in our country. Keyword: Acute Pancreatitis; Prognosis; Mortality DOI: 10.3329/jom.v12i1.6927 J Medicine 2011; 12 : 21-25